(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
The results of any case are dependent on a muti-factorial approach. There are many factors at play which need a keen understanding before the homoeopathic remedy can be prescribed and a cure achieved. Dr. C.M. Boger gave us many guidelines for constructing the portrait of the disease and the build-up to the similimum. Homeopathy remains a loyal preserver of health due to the works of it stalwarts which can be observed in all cases.